Perceiving, behaving, becoming : lessons learned - Freiberg, H. Jerome (Association for Supervision and Curriculum Development, 1999)
In 1962, ASCD's Perceiving, Behaving, Becoming: A New Focus for Education provided bold insights on the psychological foundation of education. Some of the most compelling questions in education today were first asked in this groundbreaking work, which included chapters by preeminent scholars Arthur Combs, Earl Kelley, Abraham Maslow, and Carl Rogers. Although we cannot predict what current information future generations will need to know, the book's Introduction states, creating schools that encourage the "development of persons with adequate, fully functioning personalities is the best way to contribute some degree of stability to an uncertain future." Decades later, in preparing Perceiving, Behaving, Becoming: Lessons Learned, editor H. Jerome Freiberg invited distinguished scholars in the field of affective/humanistic education and psychology to review these four chapters from the 1962 book to "provide a context for lessons learned for future generations of educators." Each author in Lessons Learned works with teachers, administrators, and schools and offers a distinct perspective on the human side of teaching and learning. Their analyses raise significant issues, such as whether an emphasis on academic standards ignores the education of the "whole" student, and what schools that are committed to an environment of trust and respect look like. Lessons Learned promises to further the cause of education that focuses on the person. By understanding the evolution of our educational past, says Freiberg, perhaps we can shape a future that will better meet the needs of generations that come after us.